Prevalence of Low Physical Fitness and Its Related Factors Among Primary School Learners in Lagos State, Nigeria - Ojedoyin, Olusegun Olatunji (My University, 2022)
Background and Purpose: Current evidence shows that physical fitness (PF) is declining among children and adolescents in Africa and worldwide, and this trend is associated with increased cardiovascular morbidity and mortality. This study aimed to evaluate the baseline PF data of primary school children in Lagos State, Nigeria, and to determine the predictors of low PF within the cohort. Materials and Methods:A total of 733 primary school children aged 6-12 years in Lagos, Nigeria, were included in this cross-sectional quantitative study. PF measures were assessed using the Eurofit battery test including sit and reach (S&R), standing long jump (SLJ), sit-ups (SU), 5 m shuttle run test (5 m-SRT), and cricket ball throw (CBT). A structured questionnaire was used to determine the socio-demographic factors. Anthropometric and cardiovascular measurements were performed using standardized protocols. Data were analyzed using descriptive statistics of frequencies, percentages, median, and quartiles, and inferential statistics of the MannWhitney U test, Quade analysis of covariance (ANCOVA) correlation matrix, and multiple linear regression model. Results:Boys showed significantly higher SU counts (P<0.001), higher CBT (P<0.001), lower 5 m SRT (P=0.003), and the same SLJ (P=0.008) than girls, while S&R scores were statistically comparable (P=0.135). Also, the results showed that sex (B=-0.647, P=0.015), height (B=0.831, P=0.0001), weight (B=-0.641, P=0.007), and hip circumference (HC) (B=0.955, P=0.009) were significantly associated with total PF (measured using S&R, SLJ, SU,5 m SRT, and CBT). Conclusion: Increased weight and gender were the main predictors of low PF among primary school children in Lagos, Nigeria.